2014
DOI: 10.1002/jbmr.2358
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal HR-pQCT and Image Registration Detects Endocortical Bone Loss in Kidney Transplantation Patients

Abstract: Patients with chronic kidney disease (CKD) who undergo kidney transplantation experience bone loss and increased risk of fracture. However, the mechanisms of this bone loss are unclear. Our objective was to use image registration to define the cortex to assess changes in cortical porosity (Ct.Po) in patients undergoing first-time kidney transplantation. We obtained serial measurements of parathyroid hormone (PTH) and bone turnover markers and used high-resolution peripheral quantitative computed tomography (HR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 38 publications
1
48
1
1
Order By: Relevance
“…This study supports recent histomorphometric [25, 26, 37, 38] and imaging studies [16, 17, 27, 39, 40] that have reported changes in cortical bone microarchitecture in individuals with CKD. In a cross-sectional study involving 38 dialysis patients, Adragao et al [25] reported high cortical porosity in 57% and reported a significant inverse relationship between femoral bone mineral density and cortical porosity.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…This study supports recent histomorphometric [25, 26, 37, 38] and imaging studies [16, 17, 27, 39, 40] that have reported changes in cortical bone microarchitecture in individuals with CKD. In a cross-sectional study involving 38 dialysis patients, Adragao et al [25] reported high cortical porosity in 57% and reported a significant inverse relationship between femoral bone mineral density and cortical porosity.…”
Section: Discussionsupporting
confidence: 79%
“…However, relatively few studies have endeavoured to use histomorphometry [25, 26] or micro-CT of bone trephine samples, or utilised non-invasive techniques [16, 17, 27] to assess cortical microarchitecture and porosity in patients with CKD G5, 5D or after kidney transplantation. In the current study, 50% of patients had changes consistent with high bone turnover on histomorphometry, accompanied by elevated PTH values, but all participants had markedly abnormal cortical microarchitecture assessed by micro-CT with relatively preserved trabecular structural parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…По сравнению с двухфотонной рентгеновской абсорбциометрией значительно более информатив ным методом исследования скелета (микроархи тектуры кости, раздельного определения объемной плотности кортикальной и трабекулярной областей, количественной оценки минеральной костной мас сы), но пока не получившего широкого внедрения в реальную клиническую практику, является пери ферическая количественная компьютерная томогра фия с высоким разрешением [53].…”
Section: диагностика костных нарушенийunclassified
“…Based on the result deduced from this study, it may be reasonable to suggest using the same time interval, and the same CACs image to monitor both osteoporosis and atherosclerosis in the general population. The high resolution pQCT (HR-pQCT) is primarily installed at major research centers and clinical radiology departments [111][112][113][114]. Using the high spatial resolution image (100 μm or less in pixel size), the resolution obtained is close to or smaller than the average trabecular thickness (100-150 μm) [12].…”
Section: Follow-up Time Using the Qctmentioning
confidence: 99%